Penggunaan Model Pembelajaran Kooperatif Tipe Group Investigation Untuk Meningkatkan Hasil Belajar Bahasa Indonesia Pada Siswa Kelas III Mis Ar-Rahman IPI - Nur Hasna (Program Studi Pendidikan Ekonomi, Universitas Flores, 2020)
This research aims to improve the results of Indonesian language learning through the use of Group Investigation Cooperative learning model in grade III students at Mis Ar-Rahman IPI. This research is a class action research that uses the Kemmis & Taggart model. Data collection techniques are performed by observation, test and documentation. Data is analyzed in a qualitative and quantitative descriptive way. The results showed that the results of Indonesian language learning through the use of Group Investigation Cooperative learning models have increased. In cycle I showed that out of 21 students, only 11 students meet the classifications criterion with a percentage of 52.38% and an average value of 67.61, and in cycle II, the average value has increased to 81.42 by The classical dictancy reaches 100%. Based on the results it can be concluded that the use of Group Investigation Cooperative learning model can improve Indonesian language learning outcomes.